2019
DOI: 10.1093/icvts/ivz302
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in drug use-associated infective endocarditis: long-term survival is negatively affected by recurrence

Abstract: OBJECTIVES The prevalence of infectious endocarditis (IE) in intravenous drug users (IDUs) is increasing, and the number of patients who need surgery is also rising. Relatively little is known about the short-term and long-term outcomes of these operations. METHODS This study is a retrospective analysis of our institutional results, focussing on risk factors for perioperative death, major adverse events and long-term survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…In contrast with the experience of Rohn et al [ 3 ], we did not find higher mortality even after multiple relapses. Moreover, since we could not identify any predictor of a futile surgery, this reinforces the concept that any patient with a complicated IE deserves surgery without delay, irrespective of its aetiology.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with the experience of Rohn et al [ 3 ], we did not find higher mortality even after multiple relapses. Moreover, since we could not identify any predictor of a futile surgery, this reinforces the concept that any patient with a complicated IE deserves surgery without delay, irrespective of its aetiology.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the long-term outcome of IDA patients is very unsatisfactory, as shown by Rohn et al [ 3 ] but, at least in large part, likely attributable to continuing drug abuse, as suggested by a 2.3 increase in the risk of death at multivariate analysis in our series.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…[13][14][15] The evidence base, however, is built largely on reports of clinical experience and expert consensus. In fact, reviews of patients undergoing surgical debridement show an association with significant morbidity and mortality, [16][17][18][19][20] with mortality being driven often by persistent sepsis. 21 A recent retrospective cohort assessing the surgical verses medical management of isolated TVE in IVDU by Shetty et al actually suggested no mortality benefit at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence base, however, is built largely on reports of clinical experience and expert consensus. In fact, reviews of patients undergoing surgical debridement show an association with significant morbidity and mortality, 16‐20 with mortality being driven often by persistent sepsis 21 …”
Section: Discussionmentioning
confidence: 99%